Synthesis and Structural Studies on Ternary Complexes of VO(IV) ZrO(IV) with Isonitrosoacetophenone-2-picoloyl-hydrazone as Primary and 1-(o-Methoxy-Anilinomethyl)-5-Phenoxybenzimidazolen as Secondary Ligand < - K. agarwal, Suresh; Chand, Subhash (Asian Journal of Chemistry, 2010)
Ternary complexes of VO(IV) and ZrO(IV) with isonitrosoacetophenone-2- picoloylhydrazone (INAPH) as primary and 1-(o-methoxyanilinomethyl)-5- phenoxybenzimidazole (MAMPB) as secondary ligand have been synthesised and characterised on the basis of analytical, magnetic and spectral studies. Analytical data suggested 1 : 1 : 1 (M-L-L') stoichiometric composition for the ternary complexes [where M = VO(IV)/ZrO(IV), L = INAPH and L' = MAMPB]. Electrolytic conductance data revealed 1 : 1 electrolytic nature of VO(IV) complexes only. However, very low values of conductance in case of ZrO(IV) complexes, indicate their non-electrolytic behaviour. Reflectance spectra of VO(IV) complexes suggested distorted octahedral geometry for them. IR spectra of the ligands and complexes showed tridentate and bidentate behaviour of the hydrazone and Mannich base ligands respectively. ZrO(IV) complexes possess hepta-coordinated structure.